2009
DOI: 10.1016/s1672-0229(08)60044-3
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review on the Mechanisms of miRNA Regulation

Abstract: MicroRNAs (miRNAs) are a class of short, endogenously-initiated non-coding RNAs that post-transcriptionally control gene expression via either translational repression or mRNA degradation. It is becoming evident that miRNAs are playing significant roles in regulatory mechanisms operating in various organisms, including developmental timing and host-pathogen interactions as well as cell differentiation, proliferation, apoptosis and tumorigenesis. Likewise, as a regulatory element, miRNA itself is coordinatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
524
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 807 publications
(576 citation statements)
references
References 79 publications
3
524
0
13
Order By: Relevance
“…Because miRNAs regulate the levels of transcripts encoding for various proteins, miRNAs can affect diverse biological processes such as cell differentiation and development, proliferation and apoptosis, tumor genesis, immune response, metabolism, as well as host-parasite interactions in general (Cai et al, 2009). …”
Section: Mechanism For Mirna Functionsmentioning
confidence: 99%
“…Because miRNAs regulate the levels of transcripts encoding for various proteins, miRNAs can affect diverse biological processes such as cell differentiation and development, proliferation and apoptosis, tumor genesis, immune response, metabolism, as well as host-parasite interactions in general (Cai et al, 2009). …”
Section: Mechanism For Mirna Functionsmentioning
confidence: 99%
“…İkincisi ise Turkiye Klinikleri J Med Sci 2016;36 (1) endojen kaynaklı olup, genellikle 22 baz uzunluğunda olan ve translasyon aşamasını baskılayan miRNA'lardır. [9][10][11][12] RNAi mekanizmasının ilk adımı, hücre sitop lazmasında uzun çift zincirli RNA'nın Dicer enzimi tarafından 20-25 bazlık küçük RNA'lara parçalan-masıdır. Endoribonükleaz bir molekül olan Dicer, RNaz III (RNase III, Ribonuclease III) enzim ailesinin üyesidir.…”
Section: Rnai Mekani̇zmasi Ve Bi̇yogenezi̇unclassified
“…MicroRNAs (miRNAs or miRs) are short, non-coding RNAs that can suppress gene expression though base pairing to the 3' untranslated regions (3'-UTR) of targets (3). An exact mapping of HCC oncogenesis and metastasis has not yet been established, but numerous previous studies have indicated that miRNAs serve key functions in HCC development (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%